2022
DOI: 10.1002/eqe.3698
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian network‐based probabilistic framework for updating aftershock risk of bridges

Abstract: The evaluation of a bridge's structural damage state following a seismic event and the decision on whether or not to open it to traffic under the threat of aftershocks (ASs) can significantly benefit from information about the mainshock (MS) earthquake's intensity at the site, the bridge's structural response, and the resulting damage experienced by critical structural components. This paper illustrates a Bayesian network (BN)-based probabilistic framework for updating the AS risk of bridges, allowing integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The results showed that the life-cycle cost tends to increase with the contribution of ASs. In addition, other studies have also explored the AS risk on various structural systems including RC buildings, [37][38][39][40] steel frames, 41 wood structures, 2 containment buildings, 42 bridges, 43,44 and critical infrastructures. 45 All their findings imply that ASs highly affect the structural response and damage condition.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the life-cycle cost tends to increase with the contribution of ASs. In addition, other studies have also explored the AS risk on various structural systems including RC buildings, [37][38][39][40] steel frames, 41 wood structures, 2 containment buildings, 42 bridges, 43,44 and critical infrastructures. 45 All their findings imply that ASs highly affect the structural response and damage condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addressing this issue, Mun and Song (2022) suggested a risk modeling approach that employs BN to consider a sequence of mainshocks and aftershocks. Tubaldi et al (2022) utilized a BN-based probability framework to update the aftershock risk of bridges. However, they did not focus on the following problem, namely, an uncertain mainshock can trigger a series of aftershocks over a long period, which is essentially a frequency problem and contradicts the purely probabilistic nature of BN.…”
Section: Introductionmentioning
confidence: 99%